An introduction to digital marketing tools and techniques - Meadows-Klue, Danny (Henry Stewart Talks, 2009)
Building on the foundations of classic marketing with new tools, without its constraints, Building brand websites that work, Measure the performance and effectiveness of web marketing, How search engine optimization works, Search engine advertising, Online advertising design, Online media planning, Marketing through social media, The law and regulation of digital marketing, Underlying theory: integrated digital marketing, Digital marketing trends
Archived at 2022/04/11